Econsota recreational and educational trail (2020)
This article is part of research project design program, through the systematization of the project developed in the workshop of social design of the first half of 2011. The proposal of appropriation of the public space in the sub urban stretch in the Consota River, near the old recreational park of Vergel in Pereira. The project involves a participative design process in COVARIC's community, whose direction is within the university Católica de Pereira, where disciplinary design methodologies were applied with a social responsibility approach.